El projecte «terradebruixes» i els processos per bruixeria andorrans: entre la recerca històrica i la divulgació. - CASTELL GRANADOS, PAU (Scripta, 2019)
The research carried out during the last decades has pointed up the relevance and uniqueness of the Andorran sources concerning the historical phenomenon of witch-hunts, by highlighting the large number of witchcraft trials preserved for the 15th-17th centuries. This archival reality has motivated the development of a research project financed by the Andorran Government and devoted to the collection and study of the totallity of witchcraft trials preserved in the series «Tribunal de Corts» of the Arxiu Nacional d'Andorra. The project's results have been displayed in a web page containing an interactive atlas and a database composed of dozens of individual files enriched with a system of tags and hyperlinks. The platform therefore becomes a powerful tool for researchers as well as an innovative experience regarding the dissemination and valorisation of research among the general public.